Synopsis: Rwanda’s food systems transformation: A diagnostic of the public policy landscape shaping the transformation process - Dusingizimana, Petronille; Kazungu, Jules; Lalui, Armin; Milani, Peiman; Munanura, James; Nsabimana, Aimable; Sindi, Julius Kirimi; Spielman, David J.; Umugwaneza, Maryse (International Food Policy Research Institute, 2022)
As Rwanda journeys towards a broad-based social and economic transformation, there are opportunities for the country’s food systems to become a key driver on that journey. This idea has attracted considerable attention in the national consultations conducted in the run-up to the United Nations Food Systems Summit (UNFSS) in September 2021, at the summit itself, in the post-summit actions that Rwanda is now pursuing, and in a series of prior case studies on Rwanda’s food system (Adolph et al. 2021; Guijt et al. 2021; Malabo Montpellier Panel 2021). This note summarizes a recent diagnostic of Rwanda’s food systems and the policy landscape that shapes them. Emphasis is placed on six inter-related clusters: diet quality and nutrition security; livelihoods equity; environmental resilience; agricultural productivity; infrastructure capacity; and financing and investment. Overall findings suggest an opportunity for a tangible shift in how public policy in Rwanda approaches its food systems and how the systems contribute to the broader national transformation process. We offer several policy recommendations to support the design of a coherent country strategy and policy framework. First, strengthen existing entities and mechanisms, and innovate on them. Second, develop a national food systems transformation strategy that is integrative, multi-sectoral, and action-oriented. Third, innovate on existing programs. Fourth, allow for learning through both success and failure. Fifth, invest in rigorous impact evaluation.